Bycatch Associated with the Artisanal Tuna Fisher of Bunaken National Park, North Sulawesi, Indonesia - Walker, Ryan C.J. (Silliman Journal, 2022)
An investigation into the bycatch produced by the rtisanal tuna fishery of Bunaken National Park was undertaken between May and July 2001. The fishery employs two types of gear: pole and line and purse seine. Mahi mahi (Coryphaena hippurus) was the most common bycatch species of the pole and line gear, while juvenile trevally (Carangoides spp.) dominated the bycatch associated with the purse seine gear. Both biomass transfer efficiency (BTE) and bycatch per unit effort (BpUE) were very low for both gears. Bycatch and wastage was very low at <1% of the catch, a stark contrast to many commercial tuna fishing operations which create high bycatch. This research supports the hypothesis that certain artisanal fishing practices can relieve local anthropogenic pressure on finfish populations in the form of bycatch and wastage and can be generally more selective in comparison to more industrial fishing methods.